Nonprofit Housing in Rural British Columbia: Needs, Opportunities, and Barriers - Čížek, Erika; Collins, Damian (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale)

(untitled) (SFU Canadian Institute for Studies in Publishing, 2025)
Community housing is central to addressing Canada’s housing affordability crisis. In rural areas, nonprofit organizations play a lead role in the provision of community housing. We conducted research in Kaslo and Nelson, rural communities in British Columbia, to determine the causes of housing affordability challenges and assess the efforts of nonprofit organizations to address them. Key informant interviews revealed that housing demand is fuelled by amenity migrants and second home owners, and that there is low availability of rental units. Efforts to increase housing supply are complicated by infrastructure limitations and high costs. Nonprofit community housing providers face barriers associated with limited capacity, funding structures, and NIMBY sentiment. We conclude that regional cooperation and funding structures that are sensitive to geographical context provide paths forward.